Agonist-Evoked Increases in Intra-Platelet Zinc Couple to Functional Responses - Ahmed, Niaz S.; Lopes Pires, Maria E.; Taylor, Kirk A.; Pugh, Nicholas (Thrombosis and Haemostasis, 2019)
Background Zinc (Zn2+) is an essential trace element that regulates intracellular processes in multiple cell types. While the role of Zn2+ as a platelet agonist is known, its secondary messenger activity in platelets has not been demonstrated.Objectives This article determines whether cytosolic Zn2+ concentrations ([Zn2+]i) change in platelets in response to agonist stimulation, in a manner consistent with a secondary messenger, and correlates the effects of [Zn2+]i changes on activation markers.Methods Changes in [Zn2+]i were quantified in Fluozin-3 (Fz-3)-loaded washed, human platelets using fluorometry. Increases in [Zn2+]i were modelled using Zn2+-specific chelators and ionophores. The influence of [Zn2+]i on platelet function was assessed using platelet aggregometry, flow cytometry and Western blotting.Results Increases of intra-platelet Fluozin-3 (Fz-3) fluorescence occurred in response to stimulation by cross-linked collagen-related peptide (CRP-XL) or U46619, consistent with a rise of [Zn2+]i. Fluoresence increases were blocked by Zn2+ chelators and modulators of the platelet redox state, and were distinct from agonist-evoked [Ca2+]i signals. Stimulation of platelets with the Zn2+ ionophores clioquinol (Cq) or pyrithione (Py) caused sustained increases of [Zn2+]i, resulting in myosin light chain phosphorylation, and cytoskeletal re-arrangements which were sensitive to cytochalasin-D treatment. Cq stimulation resulted in integrin αIIbβ3 activation and release of dense, but not α, granules. Furthermore, Zn2+-ionophores induced externalization of phosphatidylserine.Conclusion These data suggest that agonist-evoked fluctuations in intra-platelet Zn2+ couple to functional responses, in a manner that is consistent with a role as a secondary messenger. Increased intra-platelet Zn2+ regulates signalling processes, including shape change, αIIbβ3 up-regulation and dense granule release, in a redox-sensitive manner.
Keywords: platelets; zinc; platelet activation; signal transduction; secretory vesicles; granule release